Identification and Characterization of a Novel Salt-Tolerant Esterase from the Deep-Sea Sediment of the South China Sea - Zhang, Yi; Hao, Jie; Zhang, Yan-Qi; Chen, Xiu-Lan; Xie, Bin-Bin; Shi, Mei; Zhou, Bai-Cheng; Zhang, Yu-Zhong; Li, Ping-Yi (Frontiers in Microbiology, 2017)
Marine esterases play an important role in marine organic carbon degradation and cycling. Halotolerant esterases from the sea may have good potentials in industrial processes requiring high salts. Although a large number of marine esterases have been characterized, reports on halotolerant esterases are only a few. Here, a fosmid library containing 7,200 clones was constructed from a deep-sea sediment sample from the South China Sea. A gene H8 encoding an esterase was identified from this library by functional screening and expressed in Escherichia coli. Phylogenetic analysis showed that H8 is a new member of family V of bacterial lipolytic enzymes. H8 could effectively hydrolyze short-chain monoesters (C4–C10), with the highest activity toward p-nitrophenyl hexanoate. The optimal temperature and pH for H8 activity were 35°C and pH 10.0, respectively. H8 had high salt tolerance, remaining stable in 4.5 M NaCl, which suggests that H8 is well adapted to the marine saline environment and that H8 may have industrial potentials. Unlike reported halophilic/halotolerant enzymes with high acidic/basic residue ratios and low pI values, H8 contains a large number of basic residues, leading to its high basic/acidic residue ratio and high predicted pI (9.09). Moreover, more than 10 homologous sequences with similar basic/acidic residue ratios and predicted pI values were found in database, suggesting that H8 and its homologs represent a new group of halotolerant esterases. We also investigated the role of basic residues in H8 halotolerance by site-directed mutation. Mutation of Arg195, Arg203 or Arg236 to acidic Glu significantly decreased the activity and/or stability of H8 under high salts, suggesting that these basic residues play a role in the salt tolerance of H8. These results shed light on marine bacterial esterases and halotolerant enzymes.